Free trade and its implications for hunger - Dos Santos, Maria José Palma Lampreia (2021)
Free trade comprises numerous forms of elimination of trade barriers among different regions of the world. Usually, the intent is to eliminate trade barriers through construction of trade agreements that usually involve various types of international economic integration agreements – namely, free trade agreements, customs unions, common markets, economic unions, etc. The elimination of trade barriers among countries and regions, mainly in countries in development, promotes economic development by bringing new countries with competitive advantages to international commerce. As a consequence, the international supply of food generally increases; at the beginning the prices decrease and allow an increase in the demand for food, which means construction (ceteris paribus) of a new market equilibrium higher than the initial one, which will contribute to food security and reduction of hunger around the world.